Berfilsafat Sebagai Gerakan Mewujudkan Perdamaian Dunia Menurut Eric Weil - Mulyatno, Carolus Borromeus (Jurnal Orientasi Baru, 2010)
Eric Weil (1904-1977) is a French Philosopher, emigrated from Germany. In the beginning of World War II, he enlisted in French army to fight the Nazi invasion. The experience of holocaust has urged him to offer a concrete contribution for the sake of humankind. He was deeply concerned with social problems, yet his main interest was philosophy. He understood philosophy as a virtue of rational dialogue to avoid violence and barbarism. Violence prevented human person to be wise. The task of philosopher is to support dialogue between the existing discourses, and to develop rational culture marked by freedom and responsibility in creating a more peaceful world. For Weil, a philosophical reflection is essentially related to politics as well as to the whole of human life. Philosophy is a moral movement or dynamic choices for transforming the world from the state of instinctive characters to the rational state of peaceful life.